Policies and practices to transition towards Renewable Energy Communities in Positive Energy Districts - Federica Gaglione (TeMA: Journal of Land Use, Mobility and Environment, 2023)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always following a rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is a continuous update about emerging topics concerning relationships among urban planning, mobility, and environment, thanks to a collection of short scientific papers written by young researchers. The Review Notes are made up of five parts. Each section examines a specific aspect of the broader information storage within the main interests of the TeMA Journal. In particular: the Town Planning International Rules and Legislation. Positive Energy Districts has entered the scientific and policy arena to accelerate urban transitions in Europe, however their implementation remains challenging in planning processes. The PED incorporates socio-economic, technological, environmental, political, and institutional challenges that need to be addressed simultaneously as part of a holistic urban strategy. The theme of PEDs finds its first application implications in renewable energy communities on a local scale. This review focuses its attention on Renewable Energy Directive Recast which also provides for financial support for the production and self-consumption of electricity from renewable sources and on the Italian legislation on renewable energy communities governed by the Milleproroghe decree.